2009
DOI: 10.1063/1.3203999
|View full text |Cite
|
Sign up to set email alerts
|

The polarity origin of the bipolar resistance switching behaviors in metal/La0.7Ca0.3MnO3/Pt junctions

Abstract: Bipolar resistance switching behaviors in the M/La0.7Ca0.3MnO3/Pt (M=Pt, Ag, Cu, Al, Ti, and W) junctions were investigated. We found that the switching polarities of the junctions for M=Pt, Ag, and Cu were opposite to those for M=Al, Ti, and W. This phenomenon was attributed to the different Gibbs free energy of the metal oxide formation. Based on Auger electron spectroscopy measurement of the M/La0.7Ca0.3MnO3 interfaces, the switching mechanisms were further discussed in terms of metal electrode redox reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 22 publications
(54 reference statements)
3
21
0
Order By: Relevance
“…24 The BRS is attributed to the reduction-oxidation reaction at the oxygen-deficient IGZO layer. 19 When a positive voltage is applied, O 2 À ions move toward the oxygen-deficient layer. Thus, the oxygen-deficient IGZO layer is thinned down as being oxidized.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…24 The BRS is attributed to the reduction-oxidation reaction at the oxygen-deficient IGZO layer. 19 When a positive voltage is applied, O 2 À ions move toward the oxygen-deficient layer. Thus, the oxygen-deficient IGZO layer is thinned down as being oxidized.…”
mentioning
confidence: 99%
“…These generated oxygen vacancies are thought to cause BRS, triggering a reduction-oxidation reaction with oxygen ions according to the polarity of the applied voltage. 19 The nominal device area used for electrical characterization is 100 lm  100 lm. The BE is grounded while a voltage is applied to the TE.…”
mentioning
confidence: 99%
“…The oxidation near the interface plays a role in the electrical hysteresis and resistance switching. The opposite switching polarity of the Ag/PCMO/Pt device to the Al/PCMO/Pt device is due to the difference in the oxidation Gibbs free energy [41]. …”
Section: Resultsmentioning
confidence: 99%
“…Several models have been proposed to explain the physical origin of this phenomenon, such as a redox of top electrode41, change of schottky-like barrier with electrochemical migration42, redox of Metal-O-Metal conducting chain29, or Mott metal-insulator transitions43. However, increasing evidence shows that the motion of oxygen ions or vacancies in the vicinity of the electrode area plays an important role for the resistance change in perovskite manganites28293031324445. It has been reported that the RS effect of the perovskite manganite films stems from the break or repair of the -Mn 3+ -O 2− -Mn 4+ - chains induced by the electric field through the oxygen ions or vacancies migration294647.…”
Section: Discussionmentioning
confidence: 99%